2018
DOI: 10.1016/j.neuron.2018.02.015
|View full text |Cite|
|
Sign up to set email alerts
|

Tau Kinetics in Neurons and the Human Central Nervous System

Abstract: We developed stable isotope labeling and mass spectrometry approaches to measure the kinetics of multiple isoforms and fragments of tau in the human central nervous system (CNS) and in human induced pluripotent stem cell (iPSC)-derived neurons. Newly synthesized tau is truncated and released from human neurons in 3 days. Although most tau proteins have similar turnover, 4R tau isoforms and phosphorylated forms of tau exhibit faster turnover rates, suggesting unique processing of these forms that may have indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
445
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 444 publications
(496 citation statements)
references
References 80 publications
44
445
1
6
Order By: Relevance
“…We found that independent of Aβ1‐42, levels of synaptic biomarkers expressed as ratios relative to Tau, in particular, NPTX2/Tau, achieved high classification accuracy. NPTX2 is decreased in the brain and CSF in AD, reflecting the loss of a key mechanism of synaptic homeostasis, whereas CSF Tau is increased, reflecting AD‐related damage to neurons that may lead to regulated increases in the secretion of proteolytically cleaved Tau [34]. The ratio combining measures of these two processes seems to capture neurodegeneration in a way that correlates well with impaired cognitive performance, and can, therefore, track early stages of cognitive decline in AD.…”
Section: Discussionmentioning
confidence: 99%
“…We found that independent of Aβ1‐42, levels of synaptic biomarkers expressed as ratios relative to Tau, in particular, NPTX2/Tau, achieved high classification accuracy. NPTX2 is decreased in the brain and CSF in AD, reflecting the loss of a key mechanism of synaptic homeostasis, whereas CSF Tau is increased, reflecting AD‐related damage to neurons that may lead to regulated increases in the secretion of proteolytically cleaved Tau [34]. The ratio combining measures of these two processes seems to capture neurodegeneration in a way that correlates well with impaired cognitive performance, and can, therefore, track early stages of cognitive decline in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Tau tangles block the transport of nutrients and other essential molecules inside neurons. Although the complete sequence of events is unclear, beta‐amyloid may begin accumulating before abnormal tau, and increasing beta‐amyloid accumulation is associated with subsequent increases in tau 7,8 …”
Section: Overview Of Alzheimer's Diseasementioning
confidence: 99%
“…Although the complete sequence of events is unclear, beta-amyloid may begin accumulating before abnormal tau, and increasing beta-amyloid accumulation is associated with subsequent increases in tau. 7,8 Other brain changes include inflammation and atrophy. The presence of toxic beta-amyloid and tau proteins are believed to activate immune system cells in the brain called microglia.…”
Section: Brain Changes Associated With Alzheimer's Diseasementioning
confidence: 99%
“…Various mechanisms have been described by which tau aggregates can be released or taken up by cells . However, it has recently become clear that tau is released by neurons in both health and disease . This suggests that tau, apart from interacting with microtubules, has other functions as well .…”
Section: Psp: Milestones Of the Recent 10 Yearsmentioning
confidence: 99%